Introduction to Algorithmic Government - Gupta, Rajan. author. (orcid)0000-0002-9851-4047 Link aut Link
XXI, 199 p. 29 illus.
Keywords: 'The book covers the emerging and valuable domain of algorithmic government and covers important topics which have not been researched in the context of Public Service Delivery such as ethics of algorithms, use of digital twins, best practices on IoT and enterprise architecture and is therefore an important read...!' - Anjali Kaushik, PhD, Ex-Indian Air Force Officer and Professor, Management Development Institute (MDI), Gurgaon, India 'Governments’ increasing use of and reliance on algorithms for making decisions are likely to have unprecedented intended and unintended consequences for billions of citizens and millions of organizations and communities around the world. Any practitioner or researcher interested in this topic will benefit from this timely and thought-provoking book. Kudos to Rajan and Saibal for creating awareness, spreading key ideas, and sharing insights on this topic at the intersection of people, technology, information, and governments!' - Devendra Dilip Potnis, PhD, Associate Professor, School of Information Sciences, University of Tennessee at Knoxville, USA This book introduces the Algorithmic Government or Government by Algorithm, which refers to authorizing machines in the Public Sector for automated decision-making based on Artificial Intelligence, Data Science, and other technologies. It is an emerging concept introduced globally and will be considered revolutionary in the future. The book covers concepts, applications, progress status, and potential use-cases of Algorithmic Government. This book serves as introductory material for the readers from technology, public policy, administration, and management fields. Dr. Rajan Gupta is a Research and Analytics Professional, certified from INFORMS (CAP), ASA (GStat), UGC (NET), and CDC (CMC). He is currently serving as Assistant Professor at the University of Delhi, India, and is CAP Ambassador-Asia Region for INFORMS, USA. Dr. Saibal K. Pal is a Senior Scientist and former Chief Information Security Officer (CISO) at the Defence Research & Development Organization (DRDO), India.